Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.ejvssr.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Mechanical Thrombectomy Treatment of Acute Superior Mesenteric Artery Embolism

Abstract: Objective/BackgroundThis report presents a superior mesenteric artery (SMA) embolism managed by percutaneous mechanical thrombectomy (PMT).MethodsA 61 year old woman diagnosed with SMA embolism was admitted. Emboli were found in the middle and distal segments of the SMA on abdominal computed tomography angiography. Under local anaesthesia, a 6 F Rotarex system was used to remove the emboli via left brachial artery access. Emboli were successfully removed and patency was restored to the SMA and its branches.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In addition to peripheral limb arteries, Rotarex was also used in abdominal cavity artery. 15 Zhang et al 16 showed a case report about a 61-year-old woman diagnosed with superior mesenteric artery embolism. This patient was treated by percutaneous mechanical thrombectomy using a 6 F Rotarex system, and the result showed that the patient's symptoms were significantly relieved and no post-operative complications were observed and no discomfort was documented during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to peripheral limb arteries, Rotarex was also used in abdominal cavity artery. 15 Zhang et al 16 showed a case report about a 61-year-old woman diagnosed with superior mesenteric artery embolism. This patient was treated by percutaneous mechanical thrombectomy using a 6 F Rotarex system, and the result showed that the patient's symptoms were significantly relieved and no post-operative complications were observed and no discomfort was documented during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, successful results were obtained with rotarex, aspirex, and angiojet system. [18][19][20] Because we did not have hydrodynamic devices in our hospital, we performed manual aspiration embolectomy with a large diameter catheter in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, as far as we know, there are only few reports of using percutaneous mechanical thrombectomy in SMAE. Zhang et al 17 reported that PMT by the Rotarex system is a minimally invasive, safe, and effective treatment in SMAE. There are many different devices in PMT for thrombectomy.…”
Section: Discussionmentioning
confidence: 99%